Fiscal Aspects of Central Bank Independence - Christopher A. Sims (Center for Economic Studies and ifo Institute (CESifo), 2001)
Most macroeconomic models treat the central bank and the trea-sury as a unified entity. The balance sheet of the central bank is therefore implicitly treated as an accounting fiction. While this is often realistic, the central bank balance sheet has implications for central bank independence. There are wide differences in the nature of central bank balance sheets today, with the US and ESCB balance sheets nearly at the extremes. The reasons for and implications of these differences are studied here.
Keywords: 330